Femto‐Second Laser‐Based Free Writing of 3D Protein Microstructures and Micropatterns with Sub‐Micrometer Features: A Study on Voxels, Porosity, and Cytocompatibility. (16th July 2013) - Chan, Barbara Pui; Ma, Jiao Ni; Xu, Jin Ye; Li, Chuen Wai; Cheng, Jin Ping; Cheng, Shuk Han
<x xml:space="preserve">Abstract</x> Femto‐second laser‐based free‐writing of complex protein microstructures and micropatterns, with sub‐micrometer features and controllability over voxel dimension, morphology, and porosity, is reported. Protein voxels including lines, spots, and micropillars are fabricated. Laser power, exposure time, z‐position, protein and photosensitizer concentrations, but not scanning speed, are important controlling parameters. A lateral fabrication resolution of ≈200 nm is demonstrated in 2D line voxels. 3D spot voxels are ellipsoids with 400 nm lateral and 1.5 μm axial dimensions. An ascending z‐stack scanning method to verify the theoretical axial optical resolution, delineate and enhance the axial fabrication resolution of 3D structures, including square prism and cylinder micropillars, is also reported. The micropillar array presents a simple "write‐and‐seed" and table platform for cell niche studies. Fibroblasts attach to, grow on, and express adhesion to molecules on micropillar arrays without the need of matrix coating. They exhibit a more "3D" morphology comparing with that in 2D monolayer cultures and physiological functions such as matrix deposition. This work presents an important milestone in engineering complex protein microstructures and micropatterns with sub‐micrometer topological features to mimic the native matrix niche for cell‐matrix interaction studies.